Radiographic Identification of Masseteric Spur and Dental Attrition: Clinical Significance in a Retrospective Study - Anand K Jayaraj; B Srimathi; Suman J Lakshmi; Senthil K Balasubramanian; S Sam Ponraj Davidson (Journal of Indian Academy of Oral Medicine and Radiology)
Background: The relationship between masseteric spurs and tooth attrition, both clinically and radiographically, remains unclear. Moreover, the influence of demographic factors such as age and sex on the presence of masseteric spurs and attrition patterns has not been adequately addressed. Objective: The present study aimed to retrospectively assess the incidence of masseteric spur on panoramic radiographs and to investigate its possible associating factors using available patient records. Methods: A total of 3274 digital panoramic radiographs from 2018 to 2023 were retrieved for the study, of which only 180 images showing the presence of masseteric spurs were collected. Demographic details, history of attrition, and masseter hypertrophy were collected from patient records. Results: On correlating the clinical findings with those of radiographic findings, evidence of attrition in both OPG (75.6%) and clinical records (70.6%) was statistically significant. Conclusion: The presence of masseteric spurs and attrition on panoramic radiographs can be considered a possible indicator of parafunctional habits.